Analysis of NPK Content in Several Solid Bokashi Fertilizers - Sihotang, Dini Rosita; Hanik, Nur Rohimah (Jurnal Biologi Tropis, 2025)
Modern agriculture faces challenges such as declining soil quality and dependency on chemical fertilizers that harm the environment. Bokashi fertilizer, produced through the fermentation of organic materials, offers an eco-friendly solution to enhance soil fertility. This study aims to analyze the nitrogen (N), phosphorus (P), and potassium (K) content in various types of solid bokashi fertilizers made from agricultural and household waste. The research method involves an experimental approach to bokashi production, including raw material collection, mixing with EM4 (Effective Microorganism 4) solution, and fermentation for three months. After production, chemical analysis was conducted in the laboratory to measure the NPK content. The results indicate variations in N, P, and K content, with straw showing a total nitrogen content of 2.17%, potassium at 2.65%, and phosphorus at 2.43%. The highest nitrogen content was found in peanut waste (2.42%), while the lowest was in household waste (1.08%). This study demonstrates that bokashi fertilizer can be an effective and environmentally friendly alternative. Future research recommendations include exploring factors affecting nutrient content and optimizing application methods for bokashi.